Scheme of industrial wireless connections based on public network - Jie CHANG (Dianxin kexue)
Industrial wireless connections are developing in the direction of networking,digitization and intelligence,which could not be considered as just a single communication network but as important sub-systems of the automatic control systems.Based on service scenarios of the existing public wireless network,related requirements were systematically studied and the related construction direction was proposed.Then,merits and drawbacks of the existing technology systems in industrial wireless connections,also maturity of the existing technology were analyzed in detail.Lastly,the future development strategies of communication operators were put forward.